Making Sense Sensibly in Crisis Communication: How Publics’ Crisis Appraisals Influence Their Negative Emotions, Coping Strategy Preferences, and Crisis Response Acceptance - Jin, Yan (Communication research, 2010)
Despite the importance of affect in persuasion and strategic communication decision making, there is a lack of a systematic and integrated approach to understanding how discrete emotions publics experience in crises and their behavioral tendencies are associated with their cognitive appraisals. A 2 (predictability: high and low) × 2 (controllability: high and low) between-subjects experiment using a random general public sample was designed to examine the variance in publics’ affective responses, their strategies of coping with crises, and their acceptance of different organizational crisis responses, as a function of publics’ appraisal of crisis predictability and controllability. Differential influences of the cognitive appraisals were found on publics’ negative emotional responses (i.e., anger, sadness, and fright) as well as their coping strategy and organizational crisis response preferences.